2008
DOI: 10.1519/jsc.0b013e31816a5c8e
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Physiological Differences Between First Team and Reserve Soccer Players Aged 10-14 Years at the Beginning and End of the Season

Abstract: The aim of this article was to identify differences in the anthropometric and physiological characteristics of first team and reserve young soccer players (10-14 years old) at both the beginning and end of the soccer season. Body composition was calculated by measuring weight, height, skinfold, limb circumference, and joint diameter. Vo2max was estimated by Astrand's test. Sprint and jump tests were also performed. In general, first team players (FTPs) were taller and leaner. However, the most relevant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
88
6
34

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 28 publications
13
88
6
34
Order By: Relevance
“…At the age of 15, the players were approximately one year post-peak height velocity (on average), which has been associated with significant increases in serum testosterone and concurrent increases physical size (25,47). Such changes reflect a post-pubertal period of muscular development, resulting in increased sprinting, jumping and (3,22,26). Indeed the progressively stronger relationships found between 20 m sprint time and both quadriceps muscle CSA and lean body mass at each age group (Table 4), highlights the importance of muscular growth to short term, maximal sprint performance.…”
Section: Discussionmentioning
confidence: 99%
“…At the age of 15, the players were approximately one year post-peak height velocity (on average), which has been associated with significant increases in serum testosterone and concurrent increases physical size (25,47). Such changes reflect a post-pubertal period of muscular development, resulting in increased sprinting, jumping and (3,22,26). Indeed the progressively stronger relationships found between 20 m sprint time and both quadriceps muscle CSA and lean body mass at each age group (Table 4), highlights the importance of muscular growth to short term, maximal sprint performance.…”
Section: Discussionmentioning
confidence: 99%
“…Fitness testing throughout a competitive season is of great importance for the identification of strengths and weaknesses of individuals and sports teams [6]. More specifically, performance level on soccer-specific tests has been found to correlate with match performance in terms of the distance covered at high-intensity -a key determinant of physical match performances -emphasizing the value of such tests to soccer performance [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, performance level on soccer-specific tests has been found to correlate with match performance in terms of the distance covered at high-intensity -a key determinant of physical match performances -emphasizing the value of such tests to soccer performance [5,7]. The variation in fitness over the course of a season has been investigated extensively in male soccer players of different playing standard, age and nationality [6,[8][9][10][11]. In general, the existing research on male players has indicated that over the course of a season aerobic performance is improved mid-season, after which a decline is reported; whilst sprint and agility performance improve throughout the competitive season [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that affirm that exists a strong correlation between strength, sprinting, and jumping performance in several sport activities, and also in elite football player (Wisløff, Castagna, Helgerud, Jones, Hoff, 2004), (Glatthorn, Gouge, Nussbaumer, Stauffacher, Impellizzeri, Maffiuletti, 2011), (Ruiz, Pinillos, Molina, Latorre, 2015). We can say that lately, the performances in sport increased at the occurrence of using high precision equipment in measuring psychomotor qualities, such as Myotest (Gravina, Gil, Ruiz, Zubero, Gil, Irazusta, 2008), (Nuzzo, Anning, Scharfenberg, 2011), (Houel, Dinu, Faury, Seyfried, 2011. The lack of specific physical preparation is reflected in jumping without effectiveness, jumps that are not bringing any benefits while attacking and also creating problems in the defence.…”
Section: Introductionmentioning
confidence: 99%